2006
DOI: 10.1007/s12094-006-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment with transurethral resection, neoadjuvant chemotherapy followed by radiochemotherapy in stage T2-3 transitional bladder cancer

Abstract: Combined treatment provide high response rates and can be offered as an alternative option to radical cystectomy in selected patients with TCC. Patients with T2 stage and complete histologic resection in initial TURB had the best outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
6
1
1
Order By: Relevance
“…Despite the discouraging results of the RTOG Phase III trial regarding the role of neoadjuvant CT,12 several investigators from different institutions have reported on protocols that incorporated neoadjuvant CT into a multimodality treatment 19–21. Danesi et al19 evaluated a schedule of concurrent cisplatin and 5‐fluorouracil delivered by protracted intravenous infusion during hyperfractionated RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the discouraging results of the RTOG Phase III trial regarding the role of neoadjuvant CT,12 several investigators from different institutions have reported on protocols that incorporated neoadjuvant CT into a multimodality treatment 19–21. Danesi et al19 evaluated a schedule of concurrent cisplatin and 5‐fluorouracil delivered by protracted intravenous infusion during hyperfractionated RT.…”
Section: Discussionmentioning
confidence: 99%
“…This finding accords with our findings that T classification, together with resection status after TUR, had the strongest impact on overall survival. More recently, Cobo et al21 reported on 29 patients who underwent TUR and received neoadjuvant CT and RCT followed by consolidation RT when a CR was achieved. Again, those investigators reported that early‐stage disease and initial complete resection were predictive of the best outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage cystectomy ratewas 29%at 5 year [15]. In multiple series, the 5 &10-year OS for RCwas 45%-60% and 37% -45%, respectively [2][3][4][5][6][7] while, the 5-year OS for BPT utilizing trimodal therapy was 36-74% [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 92%
“…In contemporary series, 5-and 10-year overall survival for radical cystectomy is reported between 45% to 60% and 37% to 45%, respectively [2][3][4][5][6][7]. The 5-year overall survival for bladder preservation using trimodality therapy falls within a similar range at 36-74% [25,[27][28][29]33,36,37,[46][47][48][49][50]. Currently, bladder preservation appears to be a viable alternative to radical cystectomy in patients who may be poor surgical candidates or in those who may opt not to undergo radical cystectomy.…”
Section: Discussionmentioning
confidence: 98%